THE IMPACT OF MEDIA TYPE AND DOSE OF NITROGENFERTILIZER TO THE SEEDLINGGROWTH OF Accacia mangium Willd - Warsono Warsono; Sumiarjo Kiswondo; Wahyu Giri Prasetyo (UPT Penerbitan Universitas Jember, 2012)
AccaciaMagniumWilld. is one of plant species which is used for industrial rawmaterials pulp and paper. Since 1984, government has allocated 1,4 million hectares ofthis plant but the annual average abilityof Sumatera is just about (70.000 – 120.000). thegrowth and the development of acacia depend on seeds sources and the condition of soilnutrient in the media used. Themassively use of topsoil as the seedling media will makebad effect to the land, so that other alternatives which are can be used such as : sawdust,rice huskash, municipal solid wastecompost, organic material or fallenleaves ofplantscompost and dung compost is needed. N element in right amount has important rolein the growth of seed, still we need 0,46 gram/polybag (1 gram TSP/ polybag) of Pelement. Supplementaryfertilizer is given twice to 15-day-old and 30-day-oldafter weaningseedlings, the dose is 0,1 gram/polybag (0,2 gram of Urea/polybag and 0,2 gram KCL/polybag) for each of N and K element. The aims of the research are: to know the kind ofsuitable alternative media; the dose of nitrogen fertilizer and the interaction of them both tothe growth of AccaciamangiumWilld seed. The research is done in the Kranjingan village,Sumbersari sub-district, Jember at altitude ± 89 m above sea level in April to July 2009.The research usesrandomized block design which is factorialy (4x3)repeated3 times. Thefirst factor is the kind of growing media (M) which is consist of 4 experimental stage thoseare: M1= top layer of the soil (topsoil); M2=municipal solid waste, sawdust , rice huskash(1:2:1); M3=municipal solid waste, sawdust , rice huskash (2:2:0); M4:municipal solidwaste, sawdust , rice huskash (0:2:2). The second factor is the dose of nitrogen fertilizer(P) which is consist of three experimental stage those are: P0=0 gram N/ polybag (0,0 gramurea/polybag); P1 =0.09 gram N/polybag (0,2 gram urea/polybag); P2 = 0,18 gramN/polybag (0,4 gram urea/polybag). Observationalparametersinclude: height, the amountof leaf, stemdiameter which is observed on 14, 28, 42, 56, 70, and 84 HST; The lengthandnumber ofmainroot at 84 HST and the arise of crescent leaf (HST). The result of theresearch: a. alternative media M1 (topsoil which is contain of organic material that ispineleaf litter) is the best media for all of the growthobservation of seedlingsparameters; b. application offertilizer dose P1 (0,09 gram N/polybag or 0,2 gram urea/polybag) is the bestdose for all of growthobservation of seedlingsparameters and more efficient use; c. Interaction occur and MIPI treatment (topsoil alternative media which is contain ofpineleaf litter with 0,09 gram/polybag of nitrogen) is the best result especially fordiameterobservationparameters and the time when crescent leaf of the plant appear.